Writing skills for nursing and midwifery students - Taylor, Dena Bain. (Los Angele SAGE, 2013)
Based on the author's own wealth of experience this timely, engaging book helps first-time researchers to discover the excitement of grounded theory method. Fresh, innovative and clear, this book traces the history and development of grounded theory method, and examines how the method is evolving for new contexts today. It sets out the principles involved in using grounded theory method and explains the process and theory associated with coding in grounded theory. The book introduces us to the practicalities of research design, theory building, coding and writing up.
7. What is a literature review? What is a literature review and why is it important? : Questions to ask yourself about your review of literature ; Questions to ask yourself about each book or article you're reviewing -- Types of literature review : Annotated (critical) bibliography ; Summary and critique ; Comparing research studies ; Book reviews ; Evidence-based practice reports ; Comprehensive reviews -- 8. How to review the literature. Evaluating quantitative (QN) and qualitative (QL) research -- The parts of a quantitative research article and what to look for -- The parts of a qualitative research article and what to look for -- 9. An introduction to professional writing. Academic versus professional writing -- Nursing and midwifery portfolios : Formatting your portfolio ; What to include in a portfolio -- CVs and job applications : The curriculum vitae vs. the resume -- What goes into a CV? ; Application letters and CVs: some practical tips ; Specific points about application letters ; Specific points about CVs -- Clinical and agency documentation -- Witness statements -- Writing for health education -- Communicating online : Professional email communication and email etiquette ; Discussion boards, chatrooms, blogs, and other online forums -- 10. Successful presentations. Visual supports : Poster design ; Poster sample ; Poster writing style ; Visual elements of posters -- PowerPoint : PowerPoint design ; PowerPoint presentations -- Oral presentations: tips for success : 'Locating' your presentation ; Preparing to deliver ; How to perform -- Notes for multilingual speakers ; Group presentations -- 11. Reflective writing. Writing and the reflective practitioner : What is reflective writing? ; The benefits of reflective writing ; A note on personal pronouns in reflective writing ; Reflective writing exercises -- Narrative and the illness experience -- Journal writing: linking reflection to theory and practice : How to structure a journal entry ; Final example -- 12. How to write course papers: samples of student writing : What are markers looking for? -- Sample papers : 1. Writing that integrates theory ; 2. Writing a case study ; 3. Writing about pathophysiology.
Keywords: Nursing; Midwifery